Nephrolithiasis treated with RIRS on single kidney patient: A Case Report - Fransiska Roslinda Dua Neang; Ephram Sanders Alfian Siadary; Arley Sadra Telussa (Brawijaya Journal of Urology, 2023)
Abstract. Urinary stones is a common disorder and affects a considerable number of people worldwide. Nephrolithiasis (kidney stones) is one of the kidney diseases, where the discovery of stones containing crystal components and organic matrix is the biggest cause of urinary tract disorders.Case. The case of this left kidney stone was reported at WZ Johannes General Hospital, Kupang, East Nusa Tenggara, Indonesia. The patient is a 31 year old female with a single kidney, renal stone with the size measured -+ 1.2 cm (HU = 1078) at the lower calyx pole. The patient came to the ER with complaints of left flank pain and patient complaints of left lower back pain, lower left abdomen and radiating to the groin. The patient also complains of the most pain at night and often wakes up to urinate and can't hold urine so that the patient sometimes starts urinating before arriving at the bathroom, the patient's urine output is also small. The patient often complains of gritty urine and foam at the end of the urine and has time to urinate blood. RIRS surgical procedure was performed to release the stone.Conclusion. The cause of the Renal stone should be considered prior to treatment as eliminating the cause and the underlying factor will reduce the complications and recurrence rates.